A Preliminary Study Of The Influence Of HIV Infection In The Transmission Of Tuberculosis. - Mohammad, Zahiruddin; Naing, Nyi Nyi; Salleh, Rosemi; Ahmad, Norita; Hamzah, Wan Mansor; Mahmud, Roby (2002)
The human immunodeficiency virus (HIV) epidemic has had a profound influence on the epidemiology of tuberculosis (TB). The potential for HIV-associated TB cases to transmit M. tuberculosis and to produce a secondary increase in TB morbidity is unknown.